Towards a better performance measurement & management in assessing the excellence of academicians using the e-BSC - Hamid, Suraya; Yu, May Leen; Soo, Hsaio Pei; Ijab, Mohamad Taha (2008)
One of the premier universities in Malaysia is currently looking at the Balanceds Corecard (BSC), introduced by Robert Kaplan and David Norton as the performance measurement and management tool in assessing the whole spectrum of what defines an excellent organization.This study specifically researches the use of an electronic BSC system (called e-BSC) primarily in measuring the performance and excellence of academicians in this university from the perspectives of Financial, Customer, Internal Business Process (IBP) and Learning and Growth (L&G).To substantiate this research work, a survey and several interviews was conducted.The proposed performance measurement framework is introduced together with the e-BSC’s system architecture.